Perbandingan Kriteria Kataoka Safety First dan Mean Varians dalam Pembentukan Portofolio Saham Optimal - Siswanah, Emy; Abdurakhman, Abdurakhman; Maruddani, Di Asih I (Universitas Negeri Gorontalo, 2025)
The Markowitz Mean-Variance Portfolio and the Kataoka Safety-First criterion share similarities, as both serve as risk-control methods and suitable for risk-averse investors. This study compares these two approaches in constructing an optimal portfolio and evaluates their respective performances. The findings indicate that the portfolio weights derived from both methods are positive. Empirical evidence suggests that the expected return of the Kataoka Safety-First portfolio is consistently higher than that of the Mean-Variance method. However, this greater return is accompanied by a higher level of risk. Furthermore, the Sharpe and Treynor indices for the Kataoka Safety-First portfolio surpass those of the Mean-Variance method across both portfolio variations analyzed. These results confirm that the Kataoka Safety-First portfolio demonstrates superior performance compared to the Mean-Variance approach. Therefore, the Kataoka Safety-First criterion presents itself as a viable strategy for constructing an optimal portfolio tailored to risk-averse investors.